Concept Analysis of Perceived Control - Mardiyono, Mardiyono; Songwathana, Praneed; Petpichetchian, Wongchan (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2011)
Background: Perceived control is a personality characteristic that contributes psychological adjustment. It was derived from various theories, so that definitions of perceived control were ambiguous meaning. Disclosing concept of perceived control is required.Objective: The analysis aims to identify definition and use of perceived control, examine the basic attributes of perceived control, and the measurements of perceived control.Methods: Databases searched for electronic journals and books that were published from 1994 to 2010 were analyzed.Results: Perceived control is personal belief that refers to controllability on behalf of one’s self and ability to control threats or events. The use of perceived control includes maternal, pediatric, medical, surgical, psychiatric, community nursing, and pain management. Perceived control was composed of two dimensions: belief about controllability and belief about ability to control to threats.Conclusion: Instrument of Anxiety Control Questionnaire most closely corresponds to two dimensions: belief about controllability and ability to control. Defining attributes and dimensions of perceived control are useful for developing tool.Keywords: perceived control, controllability, ability to control, and agency